Transitions of Care After Critical Illness—Challenges to Recovery and Adaptive Problem Solving*. Issue 11 (14th October 2021) - Haines, Kimberley J.; Hibbert, Elizabeth; Leggett, Nina; Boehm, Leanne M.; Hall, Tarli; Bakhru, Rita N.; Bastin, Anthony J.; Butcher, Brad W.; Eaton, Tammy L.; Harris, Wendy; Hope, Aluko A.; Jackson, James; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: Investigate the challenges experienced by survivors of critical illness and their caregivers across the transitions of care from intensive care to community, and the potential problem-solving strategies used to navigate these challenges. DESIGN: Qualitative design—data generation via interviews and data analysis via the framework analysis method. SETTING: Patients and caregivers from three continents, identified through the Society of Critical Care Medicine's THRIVE international collaborative sites (follow-up clinics and peer support groups). SUBJECTS: Patients and caregivers following critical illness. INTERVENTIONS: Nil MEASUREMENTS AND MAIN RESULTS: From 86 interviews (66 patients, 20 caregivers), we identified the following major themes: 1) Challenges for patients—interacting with the health system and gaps in care; managing others' expectations of illness and recovery. 2) Challenges for caregivers—health system shortfalls and inadequate communication; lack of support for caregivers. 3) Patient and caregiver-driven problem solving across the transitions of care—personal attributes, resources, and initiative; receiving support and helping others; and acceptance. CONCLUSIONS: Survivors and caregivers experienced a range of challenges across the transitions of care. There were distinct and contrasting themes related to the caregiver experience. Survivors and caregivers used comparable problem-solving strategies to navigate the challenges encountered across the transitions of care.